Café Langit Seduh's Formulation in Building Communication Orchestration Experiential Marketing Based Marketing - Hevi Novianti; Ika Yuliasari; Hudi Santoso (International Journal of Technology and Education Research, 2025)
For the café industry, specifically Langit Seduh, the growing abundance of information and communication technology has introduced a new lease on life for the sustainability of marketing communications. The digital realm that significantly impacts the creation and preservation of its business's stability is the Instagram social media platform. The large number of Instagram users has led Langit Seduh cafe to depend on the advancements of each feature offered in its promotional activities based on experiential marketing in order to face business competition. This research seeks to examine the marketing strategy program founded on experiential marketing implemented by Langit Seduh cafe Jakarta. This research is a mixed method study with a case study approach. The research technique is conducted through observation, interviews, and surveys of informants and participants who have been selected. The findings of this research suggest that the marketing communication strategy implemented by Langit Seduh cafe Jakarta is set to develop the 9P components of the marketing mix along with sense, feel, think, act, and relate in order to create a harmonious and dynamic marketing communications.